2020
DOI: 10.1159/000510137
|View full text |Cite
|
Sign up to set email alerts
|

Is It Safe to Offer Radical Cystectomy to Patients above 85 Years of Age? A Long-Term Follow-Up in a Single-Center Institution

Abstract: With a median age at diagnosis of 73 years, bladder cancer has the highest median age of all cancers. Age alone seems to be an independent risk factor for developing the disease with peak age advancing into the range of 85 years. As demographic changes will lead to an ever more aging population in western countries, incidence of advanced age malignancies will rise. We, therefore, analyzed a contemporary radical cystectomy (RC) series at a single high-volume center on patients undergoing RC for urothelial carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In addition, previous studies have reported that among patients who underwent radical cystectomy (RC) for urothelial carcinoma of the urinary bladder (UCB), patients in the old-age (≥75–84 years) group had a better overall and cancer-specific survival than those in the oldest-age (≥85 years) group, highlighting the benefit that easier and earlier diagnosis through FH and ROS may benefit older patients by providing potentially curative therapy. 16 The same problem also exists in UTUC. Furthermore, many RNUs are performed unnecessarily because of inaccurate preoperative staging of patients with UTUC.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, previous studies have reported that among patients who underwent radical cystectomy (RC) for urothelial carcinoma of the urinary bladder (UCB), patients in the old-age (≥75–84 years) group had a better overall and cancer-specific survival than those in the oldest-age (≥85 years) group, highlighting the benefit that easier and earlier diagnosis through FH and ROS may benefit older patients by providing potentially curative therapy. 16 The same problem also exists in UTUC. Furthermore, many RNUs are performed unnecessarily because of inaccurate preoperative staging of patients with UTUC.…”
Section: Discussionmentioning
confidence: 91%
“…In line with that, urologists are often faced with the difficult decision to offer such a complex surgery to elderly patients. Even though studies have shown that RC in elderly patients is not only feasible but safe [6], the influence of age on oncological outcomes remains unclear. To provide a strategy for risk stratification and therefore select patients which may benefit in long-term outcomes, previous studies have identified several biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Since open cystectomy represents a highly complex procedure, it is known to be associated with non‐negligible morbidity 25,26 . Still, cystectomy has been shown to be safe even in the elderly patient with malignant disease and it has further been shown that perioperative complications do not necessarily impair postoperative HRQOL outcomes 27,28 . Cystectomy that is performed due to underlying benign conditions may be associated with a higher risk of morbidity and complications—for instance due to previous surgery or treatment like radiation 17,29 .…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Still, cystectomy has been shown to be safe even in the elderly patient with malignant disease and it has further been shown that perioperative complications do not necessarily impair postoperative HRQOL outcomes. 27,28 Cystectomy that is performed due to underlying benign conditions may be associated with a higher risk of morbidity and complications-for instance due to previous surgery or treatment like radiation. 17,29 Cohn et al 17 and Al Hussein et al 6 reported overall 30-day complications rates of 73% and 65.5%, respectively, of which 47% and 20.7% had Clavien-Grade-III complications or higher.…”
Section: Discussionmentioning
confidence: 99%